2014
DOI: 10.1039/c3cc49440c
|View full text |Cite
|
Sign up to set email alerts
|

A p-type Ti(iv)-based metal–organic framework with visible-light photo-response

Abstract: Here, we report a new Ti(IV)-based porous metal-organic framework (MOF) (NTU-9), which displayed strong absorption in the visible region with a bandgap of 1.72 eV. The electronic structure and bandgap were further investigated by DFT calculations. Photoelectrochemical studies indicated that NTU-9 is photoactive under visible light illumination (λ > 400 nm) and acts as a p-type semiconductor. The results demonstrated that Ti(IV)-based MOFs could be promising visible-light photocatalysts for energy conversion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
245
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(251 citation statements)
references
References 40 publications
3
245
2
1
Order By: Relevance
“…Since Garcia et al [27] proved that MOF-5 can behave as semiconductor and show photocatalytic activity for a certain reaction, considerable attention has been paid to the exploration of these inorganic-organic hybrid materials as novel photocatalyst. So far, MIL-53(M)(M= Al, Cr, Fe) [28], MIL-88B(Fe) [29], Zr-UIO-66 [30], MIL-125(Ti) [31] and NTU-9 [32] have been used as photocatalyst for the degradation of organic pollutants. However, owing to MOF's low efficiency in exciton generation, the photocatalytic performance of them is still lower than inorganic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Since Garcia et al [27] proved that MOF-5 can behave as semiconductor and show photocatalytic activity for a certain reaction, considerable attention has been paid to the exploration of these inorganic-organic hybrid materials as novel photocatalyst. So far, MIL-53(M)(M= Al, Cr, Fe) [28], MIL-88B(Fe) [29], Zr-UIO-66 [30], MIL-125(Ti) [31] and NTU-9 [32] have been used as photocatalyst for the degradation of organic pollutants. However, owing to MOF's low efficiency in exciton generation, the photocatalytic performance of them is still lower than inorganic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, research focus was placed on MOFs with visible-light photocatalytic activity. For example, it was found that MIL-88A [39], NTU-9 [40] and a series of MIL-53 MOFs (MIL-53(Fe), MIL-53(Cr) and MIL-53(Al)) [41,42] [44]. Cu 3 (BTC) 2 MOF was formed a core-shell structure with TiO 2 , and the resulting composite was used as a platform to photocatalyze gaseous reactions [45].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the concepts of MOFs as potentially active materials in semiconductor science are emerging. [22][23][24][25][26] However, the most challenging issue in MOFs is their poor electrical conductivity, which is needed to be improved to use MOF thin film as a semiconductor material. Some attempts to improve conductivity demonstrate that the conductivity of MOFs can be improved to some extent by molecular doping of the frameworks with electron acceptors, or by using some typical organic linkers.…”
Section: Introductionmentioning
confidence: 99%